The answer of the transcranial magnetic stimulation in the brain desordes: transcranial magnetic stimulation in the clinical practice (Archives of Clinical Psychiatry, 2004)
Transcranial magnetic stimulation (TMS) is a new technique capable of stimulating the brain with some advantages over existing ones. TMS is painless, non-invasive, simple to apply and, more importantly, it is considered of low risk for research in human. This new tool has been proposed to be used in several neurologic and psychiatric diseases. The mechanism of TMS action might be based on the modulation of cortical brain excitability. Therefore, brain disorders with cortical excitability dysfunction such as epilepsy, stroke, distonia, Parkinson disease, depression and schizophrenia may be benefited from this method. Some of these disorders have been extensively studied during the last decade - such as depression - but the results to date are still not strong enough to prove the real clinical benefit of this technique. TMS is still experimental and more work is needed, but in the future, TMS may become a major therapeutic tool in neuropsychiatry. The objective of the authors in this article is to review the basic principles of TMS and discuss the results of published studies about the clinical applications of TMS.